1995
DOI: 10.1182/blood.v85.3.744.bloodjournal853744
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, immunophenotype, and distribution of latently and/or productively Epstein-Barr virus-infected cells in acute infectious mononucleosis: implications for the interindividual infection route of Epstein-Barr virus

Abstract: The present study was undertaken to unequivocally demonstrate the morphology, immunophenotype, and localization of Epstein Barr virus (EBV)-infected cells as well as the type of infection (latent versus productive) in tonsils of acute infectious mononucleosis. Paraffin sections from nine cases with clinical, serologic, and morphologic evidence of EBV infection were analyzed for the detection of small transcripts, designated EBER1 & 2, and BHLF1 by in situ hybridization (ISH) using nonisotopically labeled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(79 citation statements)
references
References 15 publications
3
73
0
2
Order By: Relevance
“…However, there is now increasing evidence pointing to B lymphocytes as the likely site of persistent EBV infection, and also as the possible target of primary EBV infection [34]. Several studies have demonstrated EBV replication within the upper epithelial cell layers in oral hairy leukoplakia and are not accompanied by detectable latent infection of basal epithelial cells [35,36]. Thus, these results do not support the idea that EBV persists in epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is now increasing evidence pointing to B lymphocytes as the likely site of persistent EBV infection, and also as the possible target of primary EBV infection [34]. Several studies have demonstrated EBV replication within the upper epithelial cell layers in oral hairy leukoplakia and are not accompanied by detectable latent infection of basal epithelial cells [35,36]. Thus, these results do not support the idea that EBV persists in epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…This is important because evidence supports EBV production in salivary glands, oropharyngeal epithelial cells, and B cells in the oropharynx. [16][17][18][19][20] Person-to-person transmission of EBV is believed to occur through exchange of infected oral fluids and cells. If EBV replication in the oral cavity is inhibited by antiviral therapy, then transmission of infectious virus may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…38 Given that EBV-positive T or NK cells have been occasionally found in the tonsil and peripheral blood of IM patients, ectopic EBV infection in T or NK cells does not necessarily lead to the development of CAEBV. [39][40][41] Although EBV-infected T and NK cells in CAEBV patients and cell lines derived from them do not express the most immunodominant EBNA3 and EBNA2, they express EBNA1, latent membrane protein 1 (LMP1) and LMP2 (the latency II type EBV gene expression) that are frequently recognized by EBV-specific CTL. 3,[42][43][44][45] Hosts with normal immune functions are thus expected to have the capacity to recognize EBV-infected T and NK cells.…”
Section: Pathophysiology Of Caebvmentioning
confidence: 99%